IMPACT OF INTERNATIONALIZATION ON INNOVATIONAL TECHNOLOGIES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (EFL) - Oksana Zabolotna (Pavlo Tychyna Uman State Pedagogical University, 2017)
The article presents the ways internationalization influences introducing innovative technologies in teaching English as a foreign language (EFL). The author shows the difference between information technologies and innovative technologies which are often used interchangeably in Ukrainian methodology books. The shown difference stimulates presenting innovations in EFL teaching at two levels: direct communication (face-to-face), indirect communication (through information technology). The teacher's role is seen more as a role of facilitator of the process of constructing knowledge in the international learning community both directly and indirectly.